Analisis Indeks Pembangunan Manusia (Ipm) Terhadap Kemiskinan Di Kalimantan Barat - Paizal, Muhamad; Sahrul, Sahrul; Sukmawati, U.Sulia (JIEF : Journal of Islamic Economics and Finance, 2021)
Indonesia is a developing country, and poverty is an issue that is the focus of consideration. The issue of needs can be seen from the components that influence it. These elements combine sluggish economic development, a low human development index, and rising unemployment. Accordingly, this investigation is expected to determine the impact of the aforementioned factors. This study uses a quantitative methodology with an elucidation approach. The source of data in this test is secondary data, the data used in this test is data from 2017 – 2020. This assessment plans to determine the effect of the human development index in West Kalimantan on poverty levels using time series data. The results of the estimation analysis show that the HDI variable has a negative and significant effect on the level of poor people in West Kalimantan, HDI affects Poverty by 18.6%, the HDI variable shows a significant value of 0.001 and is smaller than 0.05, therefore H0 is rejected and Ha is accepted. It can be concluded that HDI affects the poverty rate in West Kalimantan throughout 2017 – 2020.